Implications of MicroRNAs in Oncolytic Virotherapy - Bofill-De Ros, Xavier; Rovira-Rigau, Maria; Fillat, Cristina (Frontiers in Oncology, 2017)
MicroRNAs (miRNAs) are an abundant class of small non-coding RNA molecules (∼22nt) that can repress gene expression. Deregulation of certain miRNAs is widely recognized as a robust biomarker for many neoplasms, as well as an important player in tumorigenesis and the establishment of tumoral microenvironments. The down-regulation of specific miRNAs in tumors has been exploited as a mechanism to provide selectivity to oncolytic viruses or gene-based therapies. MiRNA response elements (MREs) recognizing miRNAs expressed in specific tissues, but down-regulated in tumors, have been inserted into the 3’UTR of viral genes to promote the degradation of these viral mRNAs in healthy tissue, but not in tumor cells. Consequently, oncolytic virotherapy associated-toxicities were diminished, while therapeutic activity in tumor cells was preserved. However, viral infections themselves can modulate the miRNome of the host cell, and such miRNA changes under infection impact the normal viral lifecycle. Thus, there is an miRNA-mediated interplay between virus and host cell, affecting both viral and cellular activity. Moreover, the outcome of such interactions may be cell-type or condition specific, suggesting that the impact on normal and tumoral cells may differ. Here, we provide an insight into the latest developments in miRNA-based viral engineering for cancer therapy, following the most recent discoveries in miRNA biology. Furthermore, we report on the relevance of miRNAs in virus-host cell interaction, and how such knowledge can be exploited to improve the control of viral activity in tumor cells.